2011
DOI: 10.1111/j.1442-2018.2011.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of peer assessment as a student engagement strategy in nurse education

Abstract: This paper describes how peer assessment was implemented in an undergraduate nursing program in Ireland to enhance student engagement, and reports students' (n=37) experiences of the process. The process involved second year Bachelor of Nursing Science students developing marking criteria and marking two of their colleagues' assignments anonymously. A qualitative descriptive design using focus group interviews was used to collect data on students' experiences. Demographic data were collected through questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
0
32
0
3
Order By: Relevance
“…These findings were in line with those of Casey et al, who reported that the implementation of PA in an undergraduate nursing programme promoted student engagement in the learning process. 17 In the current study, a large number of participants believed that PA made them more dependable, respectful to their colleagues and keen to share knowledge with them. In accordance with this, Nofziger et al investigated the professional and personal reactions of students…”
Section: Problem Analysismentioning
confidence: 71%
“…These findings were in line with those of Casey et al, who reported that the implementation of PA in an undergraduate nursing programme promoted student engagement in the learning process. 17 In the current study, a large number of participants believed that PA made them more dependable, respectful to their colleagues and keen to share knowledge with them. In accordance with this, Nofziger et al investigated the professional and personal reactions of students…”
Section: Problem Analysismentioning
confidence: 71%
“…42 These activities fit well with PA, as the process improves students' critical thinking and problem-solving abilities. 17,26,43,44 Constructivist learning activities, including PA, have been shown to improve critical thinking and communication skills. 45 The interaction among the students improved their lifelong learning skills; providing feedback was also a crucial element of independent learning that provided valuable learning opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…25 PA involves learners of the same academic level in the process of determining the quality, worth, or level of success of the outcomes of learning. 26,27 It involves individuals who have attained the same general level of training or expertise, exercise no formal authority over each other and share the same hierarchic status in the institution. 28, 29 Mowl defined PA as a form of assessment that aims both to improve the quality of learning and to empower students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer grading is a well-studied pedagogical technique used in various ways depending on educational discipline and learning outcomes [2]. Peer grading provides numerous pedagogical benefits such as increasing motivation for learning course content [3,4], strengthening critical thinking skills [5], and improving the development of immediate and long-term learning aptitude [6,7].…”
Section: Introductionmentioning
confidence: 99%